Feminisms and Abya Yala women in Barcelona (2000 - 2020). Decolonial and antiracist genealogies - Llorca Ramos, Constanza Macarena (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2021)
This article presents a genealogy of Abya Yala women’s feminisms in Barcelona in the last twenty years, mainly adressing the emergence and settlement of the anti-racist and decolonial struggles of these women. To this end, we characterize the dynamics of the feminisms in Barcelona during the first years of activism of Abya Yala feminism women -first decade of 2000- we identify the process of strengthening the anti-racist and decolonial feminism of Abya Yala women in Barcelona, and finally, we inquire into the current panorama of the anti-racist and decolonial feminism of these women in Barcelona.